High Compliance with Newborn Community-to-Facility Referral in Eastern: An Opportunity to Improve Newborn Survival - Kayemba Nalwadda, Christine; Waiswa, Peter; Kiguli, Juliet; Namazzi, Gertrude; Namutamba, Sarah; Tomson, Göran; Peterson, Stefan; Guwatudde, David (PLoS ONE, 2013)
Seventy-five percent of newborn deaths happen in the first-week of life, with the highest risk of death in the first 24-hours after birth.WHO and UNICEF recommend home-visits for babies in the first-week of life to assess for danger-signs and counsel caretakers for immediate referral of sick newborns. We assessed timely compliance with newborn referrals made by community-health workers (CHWs), and its determinants in Iganga and Mayuge Districts in rural eastern Uganda. Methods: A historical cohort study design was used to retrospectively follow up newborns referred to health facilities between September 2009 and August 2011. Timely compliance was defined as caretakers of newborns complying with CHWs’ referral advice within 24-hours. Results: A total of 724 newborns were referred by CHWs of whom 700 were successfully traced. Of the 700 newborns, 373 (53%) were referred for immunization and postnatal-care, and 327 (47%) because of a danger-sign. Overall, 439 (63%) complied, and of the 327 sick newborns, 243 (74%) caretakers complied with the referrals. Predictors of referral compliance were; the newborn being sick at the time of referral- Adjusted Odds Ratio (AOR) = 2.3, and 95% Confidence-Interval (CI) of [1.6 - 3.5]), the CHW making a reminder visit to the referred newborn shortly after referral (AOR =1.7; 95% CI: [1.2 -2.7]); and age of mother (25-29) and (30-34) years, (AOR =0.4; 95% CI: [0.2 - 0.8]) and (AOR = 0.4; 95% CI: [0.2 - 0.8]) respectively. Conclusion: Caretakers’ newborn referral compliance was high in this setting. The newborn being sick, being born to a younger mother and a reminder visit by the CHW to a referred newborn were predictors of newborn referral compliance. Integration of CHWs into maternal and newborn care programs has the potential to increase care seeking for newborns, which may contribute to reduction of newborn mortality.
Keywords: Newborn Community-to-Facility Referral; Eastern Uganda; Newborn Survival